Murraya paniculata and Swinglea glutinosa as Short-Term Transient Hosts of 'Candidatus Liberibacter asiaticus' and Implications for the Spread of Huanglongbing - Cifuentes-Arenas, Juan Camilo [UNESP]; Beattie, George Andrew Charles; Pena, Leandro; Lopes, Silvio Aparecido [UNESP] (Amer Phytopathological Soc, 2019)
Murraya paniculata and Swinglea glutinosa are aurantioid hosts of the Asian citrus psyllid (ACP) Diaphorina citri, the principal vector of `Candidatus Liberibacter asiaticus' (Las). Las is the pathogen associated with huanglongbing (HLB), the Asian form of which is the most devastating disease of Citrus species and cultivars (Rutaceae: Aurantioideae). M. paniculata is a common ornamental and S. glutinosa is grown as an ornamental, a citrus rootstock, and a hedgerow fence plant. Because of the uncertain status of these plants as reservoirs of Las, a series of cross-inoculation bioassays were carried out in different environments, using infected Valencia sweet orange (Citrus x aurantium) infected shoot tops as a source of inoculum and D. citri nymphs and adults reared on M. paniculata and S. glutinosa to inoculate pathogen-free Valencia orange plantlets. In contrast to sweet orange, Las was more unevenly distributed and reached much lower titers in M. paniculata and S. glutinosa. Infections in M. paniculata and S. glutinosa were also transient. Very few insects that successfully acquired Las from M. paniculata and S. glutinosa were able to transmit the pathogen to healthy citrus. Transmission rates were low from M. paniculata (1.0%) and S. glutinosa (2.0%) and occurred only in a controlled environment highly favorable to Las and ACP using 10-day-old adults that completed their life cycle on Las-positive plants. Our study showed that in HLB-endemic areas, M. paniculata and S. glutinosa can be deemed as epidemiologically dead-end hosts for Las and are not important alternative hosts of the pathogen for transmission to citrus. However, under a combination of conditions highly favorable to Las infection and transmission and in the absence of effective quarantine procedures, these plants could eventually serve as carriers of Las to regions currently free from HLB.
Keywords: bacteriology; disease control and pest management; ecology and epidemiology; etiology